Diversity of soil seed bank and influencing factors in the nascent wetland of the Yellow River Delta - Zhu, Tao; Fang, Qing; Jia, Luhao; Zou, Yuhan; Wang, Xuehong; Qu, Chenyu; Yu, Junbao; Yang, Jisong (Frontiers in Plant Science, 2023)
Soil seed bank is the growth and reproduction source of vegetation community, playing an important role in vegetation establishment, succession and renewal, biodiversity maintenance. This study has selected the nascent wetland in the Yellow River Delta ( YRD) formed in 1996 as study area and investigated the diversity and key influencing factors of soil seed bank diversity. The study results show that: (1) The soil seed bank in the study area has a simple structure, containing relatively few species. A total of five plant species, which belong to four families and five genera, were found in this bank, with Phragmites australis and Suaeda salsa being the dominant plants. (2)All species are herbs without woody species. One herb is annual herb and the others are perennial herbs. (3) From the sea to the river, the changes rules of the overall density and diversity of the seed bank are not obvious. (4) The dispersal distance from salt and freshwater has a significant influence on the density of the soil seed bank but has no significant influence on the diversity. Meanwhile, the soil salt content has a significant negative influence on the diversity of seed banks. (5) Aboveground vegetation did not closely relationship with diversity of soil seed bank. All above results can provide basic data and scientific evidence for the conservation of vegetation communities in the nascent wetlands and vegetation restoration in the degraded wetlands in the YRD.